Sharia as Local Theology: Reflection on Acehnese Culture and Identity - Saifuddin Dhuhri (Universitas Islam Negeri Mataram, 2015)
This article elucidates local theology, which encapsulates in the work of shari’a in Acehnese contexts. The argument of this article is grounded in the Acehnese historical epochs in which Acehnese cultural identity were formulated. I argue that Acehnese shari’a is the set of local rituals, beliefs and ideas as the production of local interpretation of Islam, which responds to local cultural identity. That version of Islam works as local theology, which embodies sacred and divine values and is perceived as local identity and ideology. Building on Tibi’s, Salim’s and Nuim’s argument on shari’a and Hall’s perspective on identity and ideology, I examine the work of shari’a in Acehnese historical times, and its relation to Acehnese culture and ideology. There are four indications that shari’a holds central role in formulating the Acehnese theology, where local cultural identity and ideology are seen as part of Islamic religiosity, namely the process of Islamization of Southeast Asia, the function of local Islamic traditional boarding education (dayah), the distribution of local power, and the work of local arts. DOI: http://dx.doi.org/10.20414/ujis.v19i2.335